La conciliación procesal, analizada y comparada en las jurisdicciones penal ordinaria y penal militar en Colombia, como violación al derecho a la igualdad. (2018)
Constitutionally it has been considered that the military penal in Colombia ruled by Law 1407 of 2010, jurisdiction is determined as a peculiarity to the general competitiveness of the ordinary penal jurisdiction, as it is said that the preceding one follows that the reason of being of this special penal regime, It lies on the one hand, the particular rules of conduct to which the members of the public force are subordinate and, on the other, the close relationship between these particular rules of behaviour. The conciliation in Colombia has been developed in criminal matters from the promulgation of Law 906 of 2004 involved both pre-procedural conciliation and procedural within these mechanisms, thus providing a different view of the conflict between victim and Perpetrator, and highlighting perspectives, needs, particularities and purposes that need to be taken into account when dealing with and propitiating a process and seeking a result that solves the consequences of the crime.